PEMBELAJARAN TAHFIDZ AL-QUR’AN ANAK-ANAK DI PONDOK PESANTREN YANBU’UL QUR’AN KUDUS - Akhmad Ulul Albab; Dedi Rismanto; Amir Mukminin (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
The Tahfidz Al-Quran program is currently popular and very popular in several educational institutions. The Tahfidz Al-Quran program is a flagship program, with various program offers for acceleration and accuracy in the process of memorizing the Al-Qur'an. This tahfidz program appears at the level of early childhood education up to tertiary institutions. This study is intended to answer the questions: (1) How are the Components of Children's Tahfidz Learning at the Yanbu'ul Qur'an Kudus Islamic Boarding School? (2) How is the Tahfidz Learning Process for Children at the Yanbu'ul Qur'an Kudus Islamic Boarding School? (3) What are the Implications of the Children's Tahfidz Learning Process at the Yanbu'ul Qur'an Kudus Islamic Boarding School? The problem is discussed through a qualitative field study. The research location as a source of data through structured and free interviews, participant observation, and documentation studies. The data were analyzed using a phenomenological approach. This study shows that: (1) Children's Tahfidz learning at the Yanbuul Qur'an Kudus Islamic Boarding School has components: students, Ustad Tahfidz, Ustad murobbi, learning objectives, learning materials, learning methods and learning evaluation. (2) The tahfidz learning process: using a halaqoh which contains 12 students, mushafahah, takrir and sorogan (3) The implications of the tahfidz learning process can be seen from the results of the evaluation of the students' tahfidz learning and the students' memorization abilities. Ustad tahfidz and ustadz murobbi as facilitators in the process of supervising the students to evaluate the students' memorization results on a daily, weekly, monthly and yearly basis.